Analisa Penggunaan Aplikasi Perpajakan Berbasis Elektronik Siridoaja.Com - Eka Septia Rahmawati; Miya Dewi Suprihandani (CV ODIS, 2022)
Technological advances require Human Resources to continue to adapt to discovering new technologies in all aspects of life. Including the elements of government in government tax services. From tax services using traditional techniques to modern with digital applications. Connecting the discovery of application technology with government services is a challenge with both positive and negative impacts. The excellent effect of using technology correctly is providing efficiency and effectiveness that are very useful for human work. However, if the use of the wrong technology, it will be a boomerang that is quite detrimental to humans. Therefore, humans must be wise in using technology, including digital taxation applications that require users to use them properly and not be misused by the wrong parties.